The Role of Nrf2 in Liver Disease: Novel Molecular Mechanisms and Therapeutic Approaches - Xu, Dongwei; Xu, Min; Jeong, Seogsong; Qian, Yihan; Wu, Hailong; Xia, Qiang; Kong, Xiaoni (Frontiers in Pharmacology, 2019)
Oxidative stress and inflammation are the most important pathogenic events in the development and progression of liver diseases. Nuclear erythroid 2-related factor 2 (Nrf2) is the master regulator of the cellular protection via induction of anti-inflammatory, antioxidant, and cyto-protective genes expression. Multiple studies have shown that activation or suppression of this transcriptional factor significantly affect progression of liver diseases. Comprehensive understanding the roles of Nrf2 activation/expression and the outcomes of its activators/inhibitors are indispensable for defining the mechanisms and therapeutic strategies against liver diseases. In this current review, we discussed recent advances in the function and principal mechanisms by regulating Nrf2 in liver diseases, including acute liver failure, hepatic ischemia-reperfusion injury, alcoholic liver disease, viral hepatitis, nonalcoholic fatty liver disease, nonalcoholic steatohepatitis, and hepatocellular carcinoma.